Sentenças conflitantes em ações coletivas relativas a direitos individuais homogêneos - Severo, Álvaro Vinícius Paranhos (2014)
In this work we seek solution to a legal problem that has occurred with some frequency: final judgments, which are partially or totally divergent, uttered in collective processes relating to homogeneous individual rights, with some common replaced, participants in the two different groups processes. What is the sentence that prevails? Outrages upon res judicata by subsequent judgment also occurs at the level of individual cases, but, as demonstrated, in terms of collective processes, the solution is different.